Intimate partner violence and mental health in Bolivia - Meekers, Dominique (BioMed Central, 2013)
BACKGROUND: Latin America has among the highest rates of intimate partner violence. While there is increasing evidence that intimate partner violence is associated with mental health problems, there is little such research for developing countries. The purpose of this paper is to examine the relationship between Bolivian women’s experiences with physical, psychological, and sexual intimate partner violence and mental health outcomes. METHODS: This study analyzes data from the 2008 Bolivia Demographic and Health Survey. 10,119 married or cohabiting women ages 15–49 are included in the analysis. Probit regression models are used to assess the association between intimate partner violence and mental health, after controlling for other demographic factors and partner characteristics. The questionnaire uses selected questions from the SRQ-20 to measure symptoms of mental health problems. RESULTS: Intimate partner violence is common in Bolivia, with 47% of women experiencing some type of spousal abuse in the 12 months before the survey. Women exposed to physical spousal violence in the past year are more likely to experience symptoms of depression, anxiety, psychogenic non-epileptic seizures, and psychotic disorders, after controlling for other demographic and partner characteristics. Women who experienced sexual abuse by a partner are most likely to suffer from all mental health issues. Psychological abuse is also associated with an increased risk of experiencing symptoms of depression, anxiety, and psychogenic seizures. Women who experienced only psychological abuse report mental health problems similar to those who were physically abused. CONCLUSION: This study demonstrates an urgent need for research on the prevalence and health consequences of psychological abuse in developing countries. Our findings highlight the need for mental health services for victims of intimate partner violence. Because physical and psychological violence are often experienced concurrently, it is recommended that health providers who are treating victims of physical intimate partner violence also screen them for symptoms of potential mental health problems and refer them to appropriate mental health services.